Strategi Guru Tahfidz dalam Memperbaiki Bacaan Al-Qur’an di Taman Pendidikan Al-Qur’an (TPA) Ar-Rasyid Kota Tanjungpinang Kepulauan Riau - Muhammad Ryan Lazuardi; Alimir Alimir; Arifmiboy Arifmiboy; Fauzan Fauzan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research was conducted at the Ar-Rasyid Al-Qur'an Education Park (TPA), Tanjungpinang City, Riau Islands, to overcome problems in learning the Al-Qur'an, especially the pronunciation of hijaiyah letters, recognition of dignity, and the science of recitation. Teachers try to guide children in reading the Koran correctly, assisted by the cooperation of parents at home. The teacher uses the question and answer method to motivate students to understand and instill the laws of recitation. This research is qualitative field research with descriptive methods. Data was collected through interviews, observation and documentation, then analyzed using the steps of collecting, editing, presenting data and drawing conclusions. Data validity testing was carried out through triangulation. The research results show that the tahfidz teacher's strategy in improving Al-Qur'an reading includes utilizing time to read the Al-Qur'an before learning, muroja'ah strategies, and implementing systematic learning procedures. Teachers also carry out final assessments every semester. Implementation techniques include the jama' method for collective memorization and the Iqra' method for reading practice. The Tahfidz teacher evaluation strategy shows the existence of supporting factors and investors, such as laziness and donor coordination between the head of the foundation, teachers and students. The solutions implemented include good time management, motivation and support from TPA, teachers and parents so that students are more enthusiastic about learning the Koran at TPA Ar-Rasyid.